Identifikasi Drug Related Problems (DRPs) Pada Pasien Pediatri Penderita Epilepsi Rawat Jalan Di RSUD Embung Fatimah Kota Batam - Faizah Zalsabila; Aprilya Sri Rachmayanti; Ghalib Syukrillah Syahputra (Pusat Riset dan Inovasi Nasional, 2025)
Epilepsy is one of the most common chronic neurological disorders in children. Long-term use of antiepileptic drugs carries the risk of Drug Related Problems (DRPs) such as drug interactions, inappropriate dosing, and untreated indications. This study aimed to identify the types and incidence of DRPs in pediatric epilepsy outpatients at Embung Fatimah General Hospital, Batam. This was a descriptive, non-experimental study with a retrospective design. Data were collected from pediatric medical records (<18 years) between January–December 2024, with a total of 45 patients. DRPs were identified using the American Society of Hospital Pharmacist (ASHP) classification. Of 45 patients, the majority were aged 1–5 years (38%) and female (53%). The most frequently used antiepileptic drug was sodium valproate (56.36%). Identification DRPs included drug interactions (63.16%), untreated indications (5.26%), and inappropriate drug selection (5.26%). No cases of overdose or failure to receive medication were found. The most dominant DRP in pediatric epilepsy patients was drug interactions, particularly between valproic acid and folic acid.